Mild and Regioselective Bromination of Phenols with TMSBr. Issue 28 (28th June 2019) - Ma, Xiantao; Yu, Jing; Jiang, Mengyuan; Wang, Mengyu; Tang, Lin; Wei, Mengmeng; Zhou, Qiuju
Abstract : In this work, an unexpected promoting effect of by‐product thioether was observed, leading to a mild and regioselective bromination of phenols with TMSBr. This method can tolerate a series of functional groups such as the reactive methoxyl, amide, fluoro, chloro, bromo, aldehyde, ketone and ester groups, and has the potential to recycle the by‐product thioether and isolate the desired product under column chromatography‐free conditions. Mechanism studies revealed that O–H··· S hydrogen bond may be formed between phenol and by‐product thioether. Possibly owing to the steric hindrance effect from by‐product thioether, the electrophilic bromination at para ‐position of phenols is much favorable. Abstract : An unexpected promoting effect of by‐product thioether was observed, leading to a mild and regioselective bromination of phenols with TMSBr. The desired para ‐brominated phenols could be obtained in high selectivity (up to 99:1) by using sulfoxides bearing sterically hindered substituents.